(untitled) (KONFERENSIYA, 2025)
Aleksandr Feinberg is regarded as one of Uzbekistan’s most celebrated poets. Although he was ethnically from another nation, he contributed priceless works reflecting Uzbek culture, traditions, and everyday life. All his poems were created with deep sincerity, devoting his entire life to the development of Uzbek poetry. The poet’s childhood, accomplishments, and impact on our national literature will be examined further